The (far-) right kind of feeling: How representations of emotional experiences perform discourses in Swedish far-right alternative news media - Danielson, Magnus (Journalistica, 2025)
The growth of far-right alternative news media and its influence on political debate highlights the need to understand the role of emotions in this type of media. Emotions are central to how ideologically motivated news gains persuasive power, yet few studies have shown in detail how descriptions of emotions help shape patterns of discourse. This article addresses that gap by analysing how emotions, as represented in language, perform discourse in Swedish far-right alternative news texts. The analysis shows how these texts construct a contrast: emotions tied to the far-right are legitimized and valued, while emotions tied to the left-wing are delegitimized and devalued. In doing so, the texts define which issues deserve emotional attention, shape how readers are expected to feel about them, and portray those who respond differently as ignorant or weak of character.